UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN SELUTUI PUKA (Tabernaemontana macrocarpa Jack) TERHADAP BAKTERI Staphylococcus aureus - Yulistia Budianti Soemarie; Fitri Handayani; Edna Nur Annisa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Selutui puka plant (Tabernaemontana macrocarpa Jack) is one of the plants used as a traditional medicine. Staphylococcus aureus is one of the gram-positive bacteria that causes infection in humans. The purpose of this research is to know the antibacterial activity on ethanol extract of leaf of selutui puka to Staphylococcus aureus and to know the effective concentration which can inhibit the growth of Staphylococcus aureus bacteria. This research is an experimental research. Research phase begins with making of simplicia, making of ethanol extract of leaf of selutui puka, phytochemical screening test of ethanol extract, antibacterial activity test is done by paper disc diffusion method with concentration 5%, 10% and 15%, positive control of ampicillin 0,1%, and negative control DMSO 1%. The data obtained were analyzed descriptively. The results of the phytochemical screening test showed the extract of ethanol leaves containing alkaloids, flavonoids, tannins, saponins, and antibacterial activity test of ethanol extract of selutui puka against Staphylococcus aureus bacteria had inhibitory power at concentrations of 5%, 10% and 15% respectively 6.09 mm, 6.24 mm and 6.25 mm inadequate power category.